A three-step approach versus the inverted internal limiting membrane flap technique in large full thickness macular hole surgery: a comparative study - Dongwei Lai; Siao Tang; Chufeng Gu; Chunren Meng; Chunyang Cai; Shuai He; Qinghua Qiu (BMC Ophthalmology)
Abstract Objective To evaluate the anatomical and functional outcomes of our novel surgery (a three-step approach) and the conventional inverted internal limiting membrane flap technique (IFT) in treating large full-thickness macular holes (FTMHs). Methods This was a retrospective, consecutive, nonrandomized comparative study of patients who underwent either the novel surgery (n = 27, Group A) or IFT (n = 27, Group B). The main outcomes of MH closure rates and the best corrected visual acuity (BCVA) at 1-, 3-, and 6-month follow-up were compared between the two groups. Results At 6 months postoperatively, MH closure was achieved in 24/27 patients in Group A and 22/27 patients in Group B (88.89% vs. 81.48%, P = 0.704) with U-shaped closure rates being significantly higher in Group A (P = 0.029). The average BCVA at month 6 was 0.69 ± 0.38 (LogMAR) in Group A and 0.91 ± 0.39 in Group B (P = 0.015) with the improvement in BCVA being significantly higher in Group A (0.50 ± 0.59 vs. 0.31 ± 0.59, P = 0.045). The recovery rates of ELM were significantly higher in Group A (P = 0.026). Conclusions Our three-step approach greatly improves anatomical and functional outcomes compared with IFT. This novel surgery has a dominant advantage in earlier and higher ultimate closure rate, U-type closure rate, and ELM recovery rate, and more importantly, better recovery of BCVA.